The importance of perceived service quality in banking loyalty for large business customers - Fragata, A. (2017)
The behaviour of the large corporate banking customers when selecting the main bank and the level of their bank loyalty, are subjects that haven´t been much investigated in previous studies. Most of Portuguese large companies in our sample work with more than 5 banks and there is a positive relation between the size of the company and the number of banks used. The competition in this bank segment is fierce, so it´s important to investigate the selection of the main bank.The data showed that Banking Loyalty for large corporate banking customers depends on Perceived Service Quality, which in turn is one factor construct explained by the variety of products, reliability and by the interpersonal relationship established between the decision maker of the company and the business bank manager. There is no statistical evidence to suggest that the variables Tangibles, Responsiveness and Price conditions are important to predict Perceived Service Quality for large corporate customers. The results of his study can help banks to build a loyalty strategy towards the segment of large corporate customers.